Chromoblastomycosis: a combination therapy approach (Actualizaciones en Sida e Infectología, 2023)
Chromoblastomycosis is a chronic and subcutaneous mycosis caused by various dematiaceousfungi, In Latin America, the most frequently found species are Fonsecaea pedrosoi andCladophialophora carrionii.Treatment is a challenge because of the lack of response and recurrence in in some cases,especially in patients with extensive and chronic lesions.We report an individual with relapse of chromoblastomycosis (by Fonsecaea pedrosoi) in theright lower limb, who had undergone incomplete treatment with terbinafine and itraconazole. The patient responded favorably to retreatment with itraconazole and terbinafine combined withpartial surgical resection of the lesion and skin grafting at the surgical site.
Keywords: chromoblastomycosis, terbinafine, itraconazole. tropical wart syndrome